Sex hormone imbalance and rheumatoid arthritis in American men: a cross-sectional analysis from NHANES 2011–2016 - Wen, Pengfei; Wang, Yidian; Yang, Mingyi; Qiao, Xincun; Yang, Peng; Hu, Shouye; Liu, Lin; Yang, Zhi (Frontiers in Immunology, 2024)
BackgroundEmerging evidence suggests that sex hormones, particularly testosterone and sex hormone-binding globulin (SHBG), play a critical role in the pathophysiology of Rheumatoid arthritis (RA). However, the precise relationship between these hormonal factors and RA risk in men remains underexplored.MethodsWe conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) 2011-2016. A total of 3,110 male participants were included after excluding those with missing data on testosterone, SHBG, RA, or key covariates. Serum testosterone and SHBG levels were measured, and RA status was determined based on self-reported physician diagnosis. Multivariate logistic regression models were used to assess the association between testosterone, SHBG, and RA. Restricted cubic spline (RCS) regression was applied to explore nonlinear relationships. Subgroup and interaction analyses were performed to assess effect modifications by age, race/ethnicity, body mass index (BMI), hypertension, and poverty-income ratio (PIR).ResultsOf the 3,110 men analyzed, 191 were diagnosed with RA. Low testosterone levels (<300 ng/dL) were significantly associated with increased RA risk (OR = 2.30, 95% CI: 1.65–3.21, p < 0.001), and elevated SHBG levels (>57 nmol/L) were also associated with a higher risk of RA (OR = 1.65, 95% CI: 1.14–2.39, p = 0.008). RCS analysis indicated a nonlinear relationship between testosterone, SHBG, and RA risk, with sharp increases in RA risk at the lower ends of testosterone and SHBG levels. Interaction analyses revealed that age, race/ethnicity, hypertension, and PIR significantly modified the relationship between these hormonal factors and RA, while BMI did not exhibit any significant interaction.ConclusionThis study provides evidence that low testosterone and high SHBG levels are associated with an increased risk of RA in men. These associations are nonlinear and modified by factors such as age, race/ethnicity, hypertension, and PIR. Our findings highlight the importance of considering hormonal status in RA risk assessment and suggest potential avenues for targeted therapeutic strategies aimed at hormonal regulation.